Postpartum spontaneous pneumomediastinum and subcutaneous emphysema - Reyna-Villasmil, Eduardo (2018)
Combination of postpartum spontaneous pneumomediastinum and subcutaneous emphysema is a very rare event that mainly occurs during the second stage of labor. Symptoms usually appear during the immediate postpartum period and include acute chest pain, shortness of breath, neck swelling and subcutaneous emphysema. These symptoms may mimic fatal conditions. It is a benign clinical situation and the symptoms generally resolve spontaneously without long-term consequences. Chest X-ray is the most important diagnostic test although normal results do not rule out the diagnosis. We present the case of a 20-year-old primiparous pregnant woman with pleuritic chest pain and swelling in neck and face during the immediate puerperium. She had subcutaneous emphysema and pneumomediastinum without significant cardiorespiratory compromise. Chest X-ray and computed tomography scan confirmed the findings. The patient recovered with conservative management.